Patient-Reported Outcomes Measures, Polycystic Kidney Disease Burden, and Outcomes in Autosomal Dominant Polycystic Kidney Disease - Dorothee Oberdhan; Aaron Yarlas; Jakob B. Bjorner; Holly Krasa (Kidney Medicine, 2024)
Rationale & Objective: Using OVERTURE (NCT01430494) study data on patient-perceived health, health care utilization, and productivity in autosomal dominant polycystic kidney disease (ADPKD), this research was conducted to characterize the burden of illness in patients with ADPKD and assess whether patient-reported outcome (PRO) assessment scores predict clinical and health-economic outcomes. Study Design: Data were analyzed from a prospective, observational study. Setting & Participants: The study cohort comprised 3,409 individuals with ADPKD in 20 countries who were aged 12-78 years and were in chronic kidney disease (CKD) stages G1-G5 and Mayo risk subclasses 1A-1E. Predictors: Scores on PRO instruments, including disease-specific assessments [ADPKD-Impact Scale (ADPKD-IS), and ADPKD-Urinary Impact Scale (ADPKD-UIS)] and generic measures were assessed. Outcomes: Clinical variables [eg, height-adjusted total kidney volume (htTKV), estimated glomerular filtration rate (eGFR), and abdominal girth] and health-economic outcomes were assessed. Analytical Approach: Associations among variables were evaluated using Spearman correlations, logistic regression, and generalized linear mixed effects repeated measures models. Results: Baseline CKD stage and Mayo risk classification showed little correlation with baseline PRO scores; however, scores on disease-specific instruments and measures of physical functioning were worse at more severe CKD stages. PRO scores predicted hospitalizations and sick days at 6-18 months, with strongest associations noted for the ADPKD-IS. PRO scores were not associated with htTKV and eGFR, but worse PRO scores were associated with greater abdominal girth. Poor baseline ADPKD-IS scores were positively associated with occurrence of ADPKD-related symptoms up to 18 months, including kidney pain (OR, 5.30; 95% CI, 2.75-10.24), hematuria (OR, 4.58; 95% CI, 1.99-10.53), and urinary tract infection (OR, 4.41; 95% CI, 1.93-10.11; P < 0.001 for all). Limitations: A limitation of the study was the maximum 18 months of follow-up available to assess outcomes. Conclusions: PRO scores predicted clinical and health-economic outcomes, such as hospitalization and absence from work, underscoring the importance of quality of life assessment of individuals with ADPKD. Plain-Language Summary: Patient-reported outcomes (PROs) are increasingly recognized as important parameters for assessing the clinical and humanistic burden of autosomal dominant polycystic kidney disease (ADPKD). We analyzed data from the observational OVERTURE study to better characterize disease impact on quality of life and determine whether patient-perceived burden might predict outcomes. Scores on PRO assessment instruments predicted hospitalizations and sick days at 6-18 months, with associations strongest for the disease-specific ADPKD-Impact Scale. Compared to patients who rated their health-related quality of life as good, those with poor baseline scores were significantly more likely to report ADPKD-related signs and symptoms up to 18 months of follow-up. These findings support using disease-specific PRO assessment instruments to assess and predict the impact of ADPKD.